PENGARUH VIDEO ANIMASI HEWAN DAN JENIS MAKANANNYA TERHADAP KEMAMPUAN MENYIMAK ANAK USIA 5-6 TAHUN DI TK HARAPAN IBU NAGARI LUNANG UTARA - Ditha Fauzia; Vivi Anggraini; Elise Muryanti; Saridewi (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
The purpose of this study was to understand the effect of animated videos of animals and their types of food on the listening skills of children aged 5 to 6 years at Harapan Ibu Kindergarten, Nagari Lunang Utara. This study used a quantitative approach with a quasi-experimental design. The research subjects were 20 children divided into two groups: B2 (10 children) as the experimental class who were given treatment in the form of animated videos of animals and their types of food, and class B1 (10 children) as the control class who were not given treatment. The data collection instrument consisted of four items with four assessment categories, namely bb (1), MB (2), BSH (3), and BSB (4). Data analysis began with a normality test and a homogeneity test to ensure the distribution of similarity and variance data. After being confirmed normal and homogeneous, it was continued with a hypothesis test using a paired sample t-test and an independent sample t-test. The results of the analysis showed a higher increase in scores in the experimental group, namely an average of 52 points, compared to the control group which experienced an increase of 33 points. This clearly demonstrates that animated videos of animals and their food have a positive impact on improving early childhood listening skills. Therefore, learning media based on animated videos of animals and their food can be an effective alternative for improving language development in children aged 5-6, particularly listening skills.